Effects of isometric contraction training on hypertensive patients：A Systematic Review - Yuan, Haodong; Luo, Jiong (Quality in Sport, 2024)
Introduction: Hypertension is one of the major threats to the health of the entire population in today’s society. Poor blood pressure values represent health warnings and are also a risk factor for cardiovascular diseases such as stroke, heart disease, angina pectoris, and peripheral arterial disease. The National Cardiovascular Disease Center’s "China Cardiovascular Health and Disease Report 2023" data shows that the prevalence of hypertension in adults has reached 31.6%, with a total of 245 million patients. Moreover, studies have shown that 43.1% of the population have normal high blood pressure, with an estimated number of 4.35. The same problem occurs not only in China, but also in the statistics of the Centers for Disease Control and Prevention in the United States. Nearly 47% of the American population has hypertension. Isometric contraction training is a type of resistance training that was often considered to be avoided by hypertensive patients in previous exercise guidance. However, in recent years, research has shown that under appropriate control, it can effectively lower blood pressure. This study explores the effects of isometric contraction training on blood pressure during acute and non acute interventions by searching and organizing relevant literature, and attempts to find new strategies as non pharmacological treatments for hypertension. Based on past research, it has been found that long-term isometric contraction training has a consistent effect on lowering blood pressure. Although there are immediate changes in acute intervention studies, the duration is very short. The use of equal length contraction training or ischemic preconditioning as a non pharmacological blood pressure improvement strategy has been proven to be safe and effective, with high process controllability, and may be a more feasible strategy in the future. Aim of the study: This study aims to evaluate the relevant literature on equal length contraction training as a strategy for reducing blood pressure, explore the correlation between experimental methods and the degree of blood pressure reduction, and attempt to find more effective ways in non pharmacological treatment strategies for hypertension. Material and methods: After conducting a systematic search of the following databases, this article identified potentially qualified grey literature from Pubmed, Web of Science, and Google Scholar, as well as journals in related fields. There are no restrictions on language or publishing timeline. The retrieval strategy uses keywords, medical keywords (MeSH), and Boolean conjunctions, including isometric contract or tension, AND (Contract, Isometric or Contracts, Isometric or Isometric Contracts), and AND (Blood Pressure, High or Blood Pressures, High or High Blood Pressure or High Blood Pressures。 In addition, a literature review was conducted to further identify randomized controlled trials that met the inclusion criteria. Conclusions: IHG can significantly reduce SBP、DBP and MAP in hypertensive patients. Therefore, we recommend that this type of exercise (especially wall squatting and grip strength exercises) is considered an effective therapy for reducing arterial hypertension. The efficiency of this intervention is limited to the short term. Therefore, long-term effects (at least 1 year) should be studied.